2018
DOI: 10.1176/appi.ajp.2018.18050568
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Management of Vascular Depression

Abstract: In the next few years, the youngest of the baby boomers will reach age 65, resulting in the greatest proportion of elderly adults in US history. Concurrent with this demographic change is the growing number of adults living with chronic conditions that increase risk of vascular disease, including hypertension, obesity, hypercholesterolemia, insulin resistance and diabetes mellitus. We address how these conditions contribute to age-related cerebrovascular changes and lead to subsequent effects on mood and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…These overt differences generated mechanistic hypotheses on the role of vascular and metabolic risk factors and their involvement in the development of LLD [ 23 ]. It was postulated that cerebrovascular damage may contribute to depression in advanced age via involvement of brain regions involved in mood regulation, notably damage to subcortical regions [ 24 ]. “Vascular depression” or “subcortical ischemic depression”, due to lesions in the subcortical white and/or gray matter caused by reduced cerebral blood flow (CBF), were suggested to be particularly relevant in older individuals without a history of previous depressive episodes, i.e., LOD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These overt differences generated mechanistic hypotheses on the role of vascular and metabolic risk factors and their involvement in the development of LLD [ 23 ]. It was postulated that cerebrovascular damage may contribute to depression in advanced age via involvement of brain regions involved in mood regulation, notably damage to subcortical regions [ 24 ]. “Vascular depression” or “subcortical ischemic depression”, due to lesions in the subcortical white and/or gray matter caused by reduced cerebral blood flow (CBF), were suggested to be particularly relevant in older individuals without a history of previous depressive episodes, i.e., LOD.…”
Section: Introductionmentioning
confidence: 99%
“…VaD encompasses not only depression with cerebral small vessel disease but also post-stroke depression (PSD) and depression related to myocardial infarction and other cardiovascular diseases [ 25 ]. Although depressive symptoms in older adults (around/after age 60 years) are common, about 22% of adults with lifetime MDD meet the criteria for the VaD subtype [ 26 ], the concept of age-related VaD is still not generally accepted and it is not included in current psychiatric manuals as DSM-5 and ICD-10 [ 24 ]. The Diagnostic and Statistical Manual of Mental Disorders (DSM-V) defines major depressive disorder by the presence of depressed mood or a marked loss of interest or pleasure in activities along with five or more of the following associated symptoms: changes in appetite or weight (5% of the total body weight), sleep, energy, concentration, and psychomotor activity, feelings of inappropriate guilt or worthlessness, and recurrent thoughts of death or suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular-related depression is associated with poor response to current antidepressant treatments (104). In addition, there are no current evidence-based primary prevention pharmacotherapies for late-onset depression.…”
Section: Potential Therapeutic Targets and Interventionsmentioning
confidence: 99%
“… 18 Studies reported that only a third of older patients treated with antidepressants achieved remission, 114 , 115 and individuals with signs of frailty or vascular depression have weaker responses to antidepressants. 115 , 116 As a result, the potential benefits and risks for adverse events related to antidepressant treatments need to be regularly assessed. 117…”
Section: Depression Among Retireesmentioning
confidence: 99%